Bezpłatna gazeta „Echo Miasta” w kontekście funkcjonowania gazet bezpłatnych na polskim rynku w latach 2003-2009 - Dolska, Anna (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2009)
Free newspapers are among the publications with the highest circulation in the world. The „Echo Miasta”, operating on the market since 2005, is undoubtedly one of the more significant titles on the free press market. Taking into account the editorial success of the „Echo Miasta” it can be concluded that the press market in Poland still a place for free newspapers with a strong urban character and focus on local issues. However, the readers convinced that they are receiving a prt whosuality is comparable to that of regular, paid newspapers.
The ,,Echo Miasta" Free Newspaper in the Context of Free Newspapers Functioning on the Polish Market in 2005 2009